Joseph Beuys : Thinking Is Form: The Drawings of Joseph Beuys - Temkin, Ann; Koepplin, Dieter; Rose, Bernice; Museum of Modern Art (MoMA), New York; Museum of Contemporary Art (Los Angeles, Calif.); Museum of art Philadelphia; Art Institute of Chicago (New York : Thames and Hudson New York, 1993)
Thinking Is Form breaks through the mass of obscure writing about Joseph Beuys to introduce this legendary artist in a simple and clear manner, through his utterly individual drawings. The subject of a major touring exhibition at The Museum of Modern Art, New York, The Museum of Contemporary Art, Los Angeles, the Philadelphia Museum of Art, and The Art Institute of Chicago, Beuys's drawings are used here as the springboard for discussions of his life, art, and ideas. Some employ such unconventional mediums as hare's blood or margarine, or use the backs of evelopes or commercial stationery. Some incorporate photographs, pressed flowers, and other organic materials, emplasizing their function as a reservoir of ideas for Beuys's sculpture, actions (performance art), and other enterprises. His achievement is viewed in the broader context of European art, and his graphic works are considered chronologically as his formative medium, in relation to his work as a whole, and as autobiographical narrative. This is the first time that the disciplines of curator and connoisseur have been rigorously applied to the selection and presentation of a truly representative segment of Beuys's work. Beuys, following the strategy articulated by Duchamp, made his own life his masterwork, and his drawings that we can begin to grasp as a whole the accomplishment of a man who declared Everyone Is An Artist.
Bibliog. p. 271-273
Checklist of the Exhibition p. 257-266
Exhibitions and Actions p. 267-270
Joseph Beuys Life Course-Work Course p. 10
Engels
Exhibition. Joseph Beuys : Thinking Is Form : The Drawings of Joseph Beuys MoMA (The Museum of Modern Art) New York 21.02-04.05.1993 / MOCA (Museum of Contemporary Art) Los Angeles 06.06-15.08.1993 / Philadelphia Museum of Art Philadelphia 10.10.1993-02.01.1994 / Art Institute of Chicago 19.02-24.04.1994
Keywords: Beuys, Joseph